2017
DOI: 10.1111/caim.12221
|View full text |Cite
|
Sign up to set email alerts
|

Shifting intra‐ and inter‐organizational innovation processes towards digital business: An empirical analysis of SMEs

Abstract: The literature suggests that increasing investments in information and communication technologies (ICTs), knowledge exchange and sharing help SMEs tackle the current global and dynamic environment. Given that much of the useful knowledge resides outside the enterprises’ boundaries, these technological tools foster the gathering of big data and information. Despite these premises, few studies have considered the role of ICTs and big data in intra‐ and inter‐organizational ties and the consequent effects on ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
226
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 314 publications
(241 citation statements)
references
References 71 publications
4
226
0
11
Order By: Relevance
“…The results of this study highlight that for SMEs, digitalization is an essential factor to create radically new services. Even if SMEs may have more challenges with digitalization (Scuotto et al, ) the present findings point out that it is an impactful route toward radical service innovations. In several configurations, network of actors and resource liquefaction appeared together, which indicates that their combination may generate significant synergies when thinking about how to organize for radical service innovation.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The results of this study highlight that for SMEs, digitalization is an essential factor to create radically new services. Even if SMEs may have more challenges with digitalization (Scuotto et al, ) the present findings point out that it is an impactful route toward radical service innovations. In several configurations, network of actors and resource liquefaction appeared together, which indicates that their combination may generate significant synergies when thinking about how to organize for radical service innovation.…”
Section: Discussionmentioning
confidence: 57%
“…Digitalization of assets and data exchange between industrial buyers and suppliers facilitate “smart” servitization (Kamp and Parry, ) and thereby also changes consumer preferences and consumption (Vendrell‐Herrero, Bustinza, Parry, and Georgantzis, ). Although SMEs face significant challenges in taking full advantage of digitalization opportunities (Del Vecchio et al, ), the use of big data and relevant information and communication tools is a proven relevant factor for SMEs’ ability to increase their innovation capabilities and innovation performance (Scuotto, Santoro, Bresciani, and Del Giudice, ). Res our ce density: An important aspect of SDL involves the ability of actors to mobilize sufficient resources to create value for others or for themselves. SDL stresses the distinction between operant resources that are factors, on which operation is to be performed, as opposed to operant resources, which are employed to produce an effect (Vargo and Lusch, ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The importance of this misfit of BPM competences is increasing when considering the considerable changes in the global digital space affording new design promises and which have seen both the development of digital public assets with exponential growth and the ability to outsource structures, data and, finally, processes into the cloud. This will expose BPs to the potential of disruptive innovation and reduce process innovation latency (Scuotto et al, 2016(Scuotto et al, , 2017. Therefore, it is very likely that ambidextrous organizations will need IT-based tools and processes in order to translate technological opportunities into new process design and successful BP optimization (Vergidis et al, 2008;Van den Bergh et al, 2014).…”
Section: Guest Editorialmentioning
confidence: 99%
“…Others have suggested that with communication technology improvements the role of proximity may be altered (Wu, Kao, & Shih, 2010). For less traditional non-hierarchical collaborative relationships information communications technology (ICT) can help coordination between firms and individuals (Bogers et al, 2019;Scuotto, Santoro, Bresciani, & Del Giudice, 2017).…”
Section: Open Innovationmentioning
confidence: 99%
“…This means that access to both local buzz and global pipelines becomes important for gaining access to a more diverse pool of knowledge whilst working in close collaboration (Bathelt, Malmberg, & Maskell, 2004). Although ICT as noted above allows access to more geographically distant knowledge, in combination with increasing globalisation this has led to a more dynamic competitive situation where innovation is more important than ever (Scuotto et al, 2017). However, the quantity, complexity, and tacit nature of much of the knowledge required ensures that geographical proximity, allowing face to face interactions, remains important (Acs et al, 2013;Huggins, Johnston, & Thompson, 2012;McCann, 2008).…”
Section: Open Innovationmentioning
confidence: 99%